Reducing the Incidence of Cast-related Skin Complications in Children Treated With Cast Immobilization. Issue 8 (December 2017) - Difazio, Rachel L.; Harris, Marie; Feldman, Lanna; Mahan, Susan T.
Abstract : Background: Cast immobilization remains the mainstay of pediatric orthopaedic care, yet little is known about the incidence of cast-related skin complications in children treated with cast immobilization. The purposes of this quality improvement project were to: (1) establish a baseline rate of cast-related skin complications in children treated with cast immobilization, (2) identify trends in children who experienced cast-related skin complications, (3) design an intervention aimed at decreasing the rate of cast-related skin complications, and (4) determine the effectiveness of the intervention. Methods: A prospective interrupted time-series design was used to determine the incidence of cast-related skin complications overtime and compare the rates of skin complications before and after an intervention designed to decrease the incidence of cast-related heel complications. All consecutive patients who were treated with cast immobilization from September 2012 to September 2014 were included. A cast-related skin complications data collection tool was used to capture all cast-related skin complications. A high rate of heel events was noted in our preliminary analysis and an intervention was designed to decrease the rate of cast-related skin complications, including the addition of padding during casting and respective provider education. Results: The estimated cast-related skin events rate for all patients was 8.9 per 1000 casts applied. The rate for the total preintervention sample was 13.6 per 1000 casts which decreased to 6.6 in the postintervention sample. When examining the heel-only group, the rate was 17.1 per 1000 lower extremity casts applied in the preintervention group and 6.8 in the postintervention group. Conclusions: Incorporating padding to the heel of lower extremity cast was an effective intervention in decreasing the incidence of cast-related skin complications in patients treated with cast immobilization. Level of Evidence: Level II.